Necessary Skills for Success in Higher Learning - Md.Yunus, Aida Suraya; Ahmad Tarmizi, Rohani; Md Nor, Sharifah; Ismail, Habsah; Wan Ali, Wan Zah; Abu Bakar, Kamariah; Hamzah, Ramlah (The International Journal of Learning, 2007)
The study focuses on identifying whether other factors, apart from academic qualification, are needed to ensure success in higher learning.